Effect of Bupleurum kunmingense polysaccharides on the weight of spleen, thymus, proliferation of lymphocyte and plaque forming cell in mice - ZHANG Luo-xiu; XU Wei-min; PAN Sheng-li; DING Li; LU Yi-feng (Acta Pharmacologica Sinica; Vol 7, No 5 (September 1986): Acta Pharmacologica Sinica, 2016)
The Bupleurum kunmingense polysaccharides (BKP) injected ip 50 or 200 mg/kg qd*4 d increased the weight of mouse spleen. BKP ip 50 mg/kg qd * 4 d enhanced the proliferative response of mouse splenocytes to lipopolysaccharides (LPS) but not to ConA as measured by [3H]TdR incorporation. On the other hand, the plaque forming cells (PFC) in 2*10(7) splenocytes of mice treated with BKP were lower than that of control group. These results suggest that BKP has selective activity on immune system.